Lipid/Clay-Based Solid Dispersion Formulation for Improving the Oral Bioavailability of Curcumin - Jae Geun Song; Hye-Mi Noh; Sang Hoon Lee; Hyo-Kyung Han (MDPI AG, 2022)
This study was conducted to develop a lipid/clay-based solid dispersion (LSD) formulation to enhance the dissolution and oral bioavailability of poorly soluble curcumin. Krill oil and aminoclay were used as a lipid and a stabilizer, respectively, and LSD formulations of curcumin were prepared by an antisolvent precipitation method combined with freeze-drying process. Based on the dissolution profiles, the optimal composition of LSD was determined at the weight ratio of curcumin: krill oil: aminoclay of 1:5:5 in the presence of 0.5% of D-α-tocopherol polyethylene glycol succinate. The structural and morphological characteristics of the LSD formulation were determined using X-ray powder diffraction, differential scanning calorimetry, and scanning electron microscopy. Crystalline curcumin was changed to an amorphous form in the LSD formulation. At the pH of acidic to neutral, the LSD formulation showed almost complete drug dissolution (>90%) within 1 h, while pure curcumin exhibited minimal dissolution of less than 10%. Furthermore, the LSD formulation had significantly improved oral absorption of curcumin in rats, where Cmax and AUC of curcumin were 13- and 23-fold higher for the LSD formulation than for the pure drug. Taken together, these findings suggest that the krill oil-based solid dispersion formulation of curcumin effectively improves the dissolution and oral bioavailability of curcumin.